Licensing policy and platform models of telemedicine: A multi-case study from China - Wang, Zhong; Xu, Rui; Liu, Yan; Li, Yiming (Frontiers in Public Health, 2023)
As a form of platform economy, telemedicine is not growing as fast as other digital platforms. Existing literature seldom pays attention to how licensing policy affects the development of telemedicine platform models. This paper uses the method of multi-case study and the theory of policy implementation as mutual adaptation to research the influence mechanism of telemedicine platform licensing policy on platform model in China. The study finds: (1) Three models can be classified in accordance with different platform providers in China: medical institution platform, Internet company platform and local government platform; (2) Bargaining power, reputation mechanism and resource specificity are important dimensions in the analysis of platform models; (3) As implementer in the process of licensing policy, the platform provider cannot only directly determine the establishment and formation of platform model, but also indirectly affect the sustainable development of platform model through affected the supplier and the demander of platform; (4) The impact between licensing policy and platform model is dynamic and bidirectional, mainly exerted via administrative orders, market-oriented mechanism and medical insurance. The research enlightens practical exploration in telemedicine and enriches the theoretical innovation in platform.